The Effect of Asset Structure, Size, Growth and Profitability of The Company on The Capital Structure of Manufacturing Companies - Dikdik Sidik Pamungkas (Return : Study of Management, Economic and Bussines, 2023)
The purpose of this study is to analyze empirical factors that affect capital structure in manufacturing companies in Indonesia. In this study the independent variables are asset structure, company size, growth and profitability. The dependent variable is the capital structure defined as the ratio of debt to assets. The population in this study is manufacturing companies listed on the Indonesia Stock Exchange during 2007-2016. There were 181 manufacturing companies, using purposive sampling method, 119 manufacturing companies used as a sample of selected population companies that had never been delisted from the Indonesia Stock Exchange during 2007-2016. The sample type is panel data, which is a combination of cross section data with time series data. This research uses quantitative methods and data analysis using panel data regression with a fixed effect model approach. The result is that asset structure, company size and profitability have a significant negative influence on the debt-to-asset ratio, but the growth shows no significant influence of about 69.27% between all independent variables with dependent variables and 30.73% contributed by other parties. Independent variables exclude asset structure, company size, growth and profitability.